Nutritional adequacy of animal-based and plant-based Asian diets for chronic kidney disease patients: a modeling study - Khor, Ban-Hock; Dina A. Tallman; Tilakavati Karupaiah; Pramod Khosla; Maria Chan; Joel D. Kopple (MDPI, 2021)
Plant-based low protein diets (LPDs) have gained popularity for managing chronic kidney disease (CKD) patients. The nutritional adequacy of these and other LPDs prescribed for CKD patients have not been carefully examined. This study assessed the nutrient composition of such LPDs and moderately high protein diets (MHPDs) that might be prescribed for patients in the Asia Pacific region with CKD who are not dialyzed or undergoing maintenance dialysis. Conventional diets containing at least 50% animal-based proteins and plant-based diets were also planned with protein prescriptions of 0.5 to 0.8 g/kg/day and MHPDs with protein prescriptions of 1.0 to 1.2 g/kg/day. Plant-based, lacto-, ovo-, and lacto-ovo-vegetarian and vegan LPDs and MHPDs were planned by replacing some or all of the animal proteins from the conventional diet. With 0.5 g protein/kg/day, all diets were below the Recommended Dietary Allowances (RDA) for at least one essential amino acid (EAA). At a protein prescription of 0.6 g/kg/day, only the conventional LPD met the RDA for all EAAs. This deficiency with the plant-based LPDs persisted even with several plant food substitutions. With a protein prescription ≥0.7 g/kg/day, all the plant-based and vegetarian LPDs provided the RDA for all EAA. The plant-based and vegetarian diets also contained relatively greater potassium, phosphorus, and calcium content but lower long-chain n-3 polyunsaturated fatty acids and vitamin B-12 than the conventional diet. Other essential micronutrients were commonly below the RDA even at higher protein intakes. The low contents of some essential micronutrients were found in both animal-based and plant-based diets. Prescription of all LPDs for CKD patients, especially plant-based and vegetarian LPDs, requires careful planning to ensure the adequacy of all nutrients, particularly essential amino acids. Consideration should be given to supplementing all animal-based and plant-based LPDs and MHPDs with multivitamins and certain trace elements.